Melatonin The Hormone of Darkness and its Therapeutic Potential and Perspectives - Vlachou, Marilena (Physiology, 2020)
This book, on the pineal hormone melatonin, is addressed to a wide non-cognizant and cognizant readership. The hormone appears to be involved in sleep onset and other functions associated with the body's clock, the suprachiasmic nucleus. It is ubiquitous throughout both the animal and plant kingdoms and has a long evolutionary history as a hormone. Melatonin has a major role in the regulation of circadian rhythms in non-mammalian vertebrates and forms part of their control in mammals. The present text emphasizes the positive role of exogenously administered melatonin, and its synthetic derivatives, on disrupted circadian rhythm-related dysfunctions. This is effected by resetting the clock in jet lag sufferers and those with seasonal affective disorders, insomnia, and various neurological conditions.